Hyaenodonta from the Middle to Late Miocene deposits of the Siwaliks of Pakistan with a brief account of Indian subcontinent hyaenodonts - Khalid Mahmood; Sayyed Ghyour Abbas; Steven E. Jasinski; Muhammad Adeeb Babar; Muhammad Akbar Khan (PalZ, 2026)
New fossil material identified as ‘creodonts,’ particularly hyaenodonts, from the Siwaliks of Pakistan provide significant new information on this important group of carnivores. Three hyaenodont taxa are identified based on these new fossils. Deciduous dental remains identified as ? Megistotherium/Hyainailouros sp. provide important new data on large hyaenodonts and their presence in the Miocene of southern Asia. Fossils identified as Hyaenodon cf. H . pervagus potentially provide important new temporal and biogeographic data on a highly speciose genus of hyaenodont. While the genus is known throughout much of the Northern Hemisphere (Asia, Europe, North America), these new fossils represent the first record of the genus from the Siwaliks, expanding its range in southern Asia. They also represent the youngest temporal occurrence of the genus (Middle Miocene). Another fossil represents a new species, Metapterodon anari sp. nov. This genus was previously tentatively identified from the Siwaliks, but this new material provides definitive evidence of its presence. Not only does this confirm its presence in the Miocene Siwalik deposits of the Indian subcontinent but also represents an important temporal occurrence for the genus. It represents the youngest occurrence of the genus worldwide but may also represent the youngest occurrence of any hyaenodont. The new material provides important new data on some of the less well-known ‘creodonts’ of the Siwaliks, and this data is important for not only our understanding of some of the youngest hyaenodonts near their eventual extinction, but the complex mammal communities preserved on the Indian subcontinent.